Larangan Peredaran Minuman Keras dalam Peraturan Daerah Kabupaten Gresik Nomor 15 Tahun 2002 Perspektif Pemikiran Syafi’iyah - Dhofirul Yahya (Jurnal Darussalam: Jurnal Pendidikan, Komunikasi dan Pemikiran Hukum Islam, 2018)
Research objectives: 1) to analyze the concept of the prohibition of liquor distribution in the district regulation of Gresik number 15 of 2002 concerning the prohibition of the distribution of liquor. 2) to analyze the prohibition of the distribution of liquor in the regional regulation, including the prohibition of the category of Syafi'iyah's perspective. The research method used is descriptive-analytical analysis, analyzed using a deductive mindset which begins with the theory of the concept of prohibiting khamar from the perspective of Syafi'iyah's thought and then drawn to the theory then drawn conclusions. The results of this study conclude 1). The concept of prohibiting the distribution of liquor in the Gresik regulation is prohibited, including Prohibition for individuals or legal entities to produce, distribute, trade, offer, hoard, store, mix, entertain, carry and/or drink liquor. The prohibition here applies to all regions of Gresik regency which includes all residents of Gresik district and all residents of other regions and/or other people in the district of Gresik. 2) Prohibition of the distribution of liquor in the Gresik regional regulation in general, including the prohibition of alcoholic categories in Syafi'iyah's perspective